A novel self-tuning wind energy harvester with a slidable bluff body using vortex-induced vibration. (1st February 2020) - Sun, Wan; Seok, Jongwon
Highlights: Development of a self-tuning technique using the balance of drag and centrifugal forces. Design and manufacture of a flexible beam fitted with a slidable bluff body. Investigation of the VIV mechanism due to the actions of the two forces exerted on the bluff body. Experimental identification of the broadband mechanism in the lock-in range for VIV. Increment of 110% in overall average output power compared to the reference case. Abstract: In this study, we propose a novel self-tuning vortex-induced vibration (VIV)-based piezoelectric energy harvesting system with a slidable bluff body configured in a circular cylinder to improve the output energetic performance. Unlike common frequency tuning techniques, we use the balance of the two inherent forces in a vibratory VIV-based energy harvester under operation, i.e., drag and centrifugal forces. First, we theoretically investigate the force and response characteristics of the system to estimate the range of the essential design parameters. Subsequently, a series of measurements are carried out to validate the effectiveness of the proposed system. The sliding mechanism of the bluff body due to the action of the two forces is thoroughly explained using both theoretical and experimental investigations. The sliding mechanism, both in the inner and outer directions, is understood through measurements performed with different bluff body heights. The results reveal that a structural natural frequency range of approximately 6–10 Hz and a broadband lock-in range of approximately 1–2.7 m/s can be realized with the parameters considered in this study. The experimental results show that a significant overall average power increase of 110% is obtained for the proposed energy harvester with the dimensionless bluff body height of 1.5 compared to the reference system in the wind velocity range of concern.